2021
DOI: 10.3390/metabo11080545
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Plasma Metabolic Profile Demarcates a Role for Neuroinflammation in Non-Typical Development of Children

Abstract: Maternal and cord plasma metabolomics were used to elucidate biological pathways associated with increased diagnosis risk for autism spectrum disorders (ASD). Metabolome-wide associations were assessed in both maternal and umbilical cord plasma in relation to diagnoses of ASD and other non-typical development (Non-TD) compared to typical development (TD) in the Markers of Autism risk in Babies: Learning Early Signs (MARBLES) cohort study of children born to mothers who already have at least one child with ASD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 142 publications
(159 reference statements)
0
8
0
Order By: Relevance
“…The existing targeted metabolomics studies have focused on individual metabolites in the pathways related to polyunsaturated fatty acids (PUFA) and inflammation, and have focused on autism spectrum disorders (ASD) or traits and neurodevelopmental delay [18][19][20]. Similarly, while the untargeted metabolomic studies have covered a much larger number of metabolic pathways, they are also limited to studying individual metabolites and ASD or non-typical neurodevelopment [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing targeted metabolomics studies have focused on individual metabolites in the pathways related to polyunsaturated fatty acids (PUFA) and inflammation, and have focused on autism spectrum disorders (ASD) or traits and neurodevelopmental delay [18][19][20]. Similarly, while the untargeted metabolomic studies have covered a much larger number of metabolic pathways, they are also limited to studying individual metabolites and ASD or non-typical neurodevelopment [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, none of the existing studies have taken advantage of multivariate supervised analytical methods that have become the mainstream of metabolomics analyses, such as orthogonal partial least squares (O-PLS) analysis. Hence, variation in the individual metabolites of the mother during pregnancy examined in the previous studies [ 18 22 ] may not have necessarily reflected the metabolomic variation specific to maternal obesity or higher BMI during pregnancy, and has not accounted for the correlated nature of the metabolomic measures. O-PLS overcomes these limitations as it reduces data dimensions and finds latent variables that maximize the correlation between the predictors and the outcome, while taking advantage of an orthogonal signal correction filter to remove variation in the predictors that are not explained by the outcome [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… 37 Lower maternal 3-OHB concentrations in the third trimester might indicate dysregulated maternal lipid metabolism, resulting in reduced availability of important lipid substrates for brain development. While this analysis was limited to the polar metabolome, a 2021 study 38 reporting on the untargeted metabolomic analysis of maternal third trimester plasma showed that higher levels of fatty acids involved in lipid biosynthesis were associated with reduced risk of non-TD in the MARBLES cohort. Taken together, these findings suggest that disturbed lipid metabolism during late pregnancy could play a role in the etiology of non-TD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the cohort includes children who did not develop ASD, but who were otherwise non-typically developing. A recent study of maternal third trimester plasma collected as part of the MARBLES study has identified alterations in the prostaglandin pathway related to non-typical development [44].…”
Section: Introductionmentioning
confidence: 99%